Evaluation of a multi‐step catalytic co‐processing hydrotreatment for the production of renewable fuels using Category 3 animal fat and used cooking oils. (9th November 2022) - ; Koutsoumanis, Konstantinos; Allende, Ana; Bolton, Declan; Bover‐Cid, Sara; Chemaly, Marianne; Davies, Robert; De Cesare, Alessandra; Herman, Lieve; Hilbert, Friederike; Lindqvist, Roland; Nauta, Maarten; et al.
Abstract: An alternative method for the production of renewable fuels from rendered animal fats (pretreated using methods 1–5 or method 7 as described in Annex IV of Commission Regulation (EC) No 2011/142) and used cooking oils, derived from Category 3 animal by‐products, was assessed. The method is based on a catalytic co‐processing hydrotreatment using a middle distillate followed by a stripping step. The materials must be submitted to a pressure of at least 60 bars and a temperature of at least 270°C for at least 4.7 min. The application focuses on the demonstration of the level of reduction of spores from non‐pathogenic spore‐forming indicator bacterial species ( Bacillus subtilis and Desulfotomaculum kuznetsovii ), based on a non‐systematic review of published data and additional extrapolation analyses. The EFSA BIOHAZ Panel considers that the application and supporting literature contain sufficient evidence that the proposed alternative method can achieve a reduction of at least 5 log10 in the spores of B. subtilis and a 12 log10 reduction in the spores of C. botulinum . The alternative method under evaluation is considered at least equivalent to the processing methods currently approved in the Commission Regulation (EU) No 2011/142.